2013
DOI: 10.1016/j.jpainsymman.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Sedation (CS) Until Death: Mapping the Literature by Bibliometric Analysis

Abstract: This is the first bibliometric analysis on continuous sedation until death that can be used to inform future studies. Further research is needed to refine controversies on terminology and ethical acceptability of the practice, as well as conditions and modalities of its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
0
22
0
2
Order By: Relevance
“…The term "palliative sedation" started to appear in the literature in 2000 (87,88). Over the years, many other terms have been used to describe sedation for symptomatic relief at the end of …”
Section: Palliative Sedation: Deep and Continuous Sedation For Reliefmentioning
confidence: 99%
“…The term "palliative sedation" started to appear in the literature in 2000 (87,88). Over the years, many other terms have been used to describe sedation for symptomatic relief at the end of …”
Section: Palliative Sedation: Deep and Continuous Sedation For Reliefmentioning
confidence: 99%
“…The heterogeneity in the literature's terminology used to define and describe “palliative sedation” is problematic (Hallenbeck, 2000; Claessens et al, 2008; Twycross, 2019. A previous review indicated more than 50 definitions, such as palliative, terminal, continuous, controlled, and deep-sleep sedation (Papavasiliou et al, 2013). According to the European Association for Palliative Care, palliative sedation is solely used to treat refractory symptoms with intentional sedation either intermittently or temporarily or continuously for terminally ill patients usually until death (Abarshi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increasing trends of CDS practice, only three studies could be identified. It is hardly surprising that these were either Dutch or Japanese, as bibliometric analysis has shown that best evidence of CDS research activity originated in the Netherlands and Japan [40]. Across the reviewed studies no shared target outcome measure for professionals’ well-being was available.…”
Section: Discussionmentioning
confidence: 99%